ANALISIS MALPRAKTIK PENETAPAN PEROLEHAN KURSI PARTAI POLITIK DAN CALON TERPILIH ANGGOTA DPRD KABUPATEN INTAN JAYA DALAM PEMILU LEGISLATIF TAHUN 2019 - Nasrullah Kutanggas; Akbar Silo; Nur Aedah (JURNAL KEBIJAKAN PUBLIK, 2023)
The General Election Commission, hereinafter abbreviated as KPU, is a national, permanent, and independent election management body whose task is to carry out elections. Election violations are actions that conflict, violate, or are not by the laws and regulations governing elections. The purpose of this study is to analyze and describe the implementation of the KPU Regulation No. 5 of 2019 in the 2019 legislative elections in the Intan Jaya Regency. This study used qualitative research methods. The focus of this research is electoral malpractice and what factors lead to electoral malpractice in the implementation of determining the acquisition of seats for political parties and elected candidates for DPRD members of Intan Jaya Regency in the 2019 legislative elections. The types and sources of data used in this study are data primary and secondary data. Informants in this study are election organizers, election supervisors, and election participants. Data collection techniques in this study are through observation, interviews, and documentation. Data analysis techniques in this study are data reduction, data presentation, and conclusion/verification. The results of this study indicate that there was election malpractice committed by the Intan Jaya district KPU commissioner regarding the process of determining the acquisition of political party seats and the determination of elected candidates for the Intan Jaya district DPRD members in the 2019 legislative elections, in the form of vote manipulation. Factors that cause election malpractice are negligence, deliberate, and intimidation of election organizers.